PERADILAN SMALL CLAIM COURT (GUGATAN SEDERHANA) DALAM HUKUM ACARA PERDATA INDONESIA - PL Tobing (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
Small Claims Court is a mechanism for settling disputes quickly so examined in small claims court are certainly cases that simple. In Article 1 number 1 of the Supreme Court Regulation Number 2 of 2015 it is stated that the Settlement of Simple Lawsuits is defined as